Growing up with a disability following paralytic poliomyelitis: experiences from persons with late effects of polio. Issue 7 (27th March 2021) - Sjödahl Hammarlund, Catharina; Lexell, Jan; Brogårdh, Christina
Abstract: Purpose: To describe the experiences of growing up after acute paralytic poliomyelitis and strategies used to adapt to the new situation. Methods: Seven women and seven men (mean age 70 years, min–max 61–78 years) with late effects of polio, who had contracted paralytic polio in their childhood. Data were collected using semi-structured interviews, transcribed verbatim, and analyzed by systematic text condensation. Results: Memories of contracting acute paralytic poliomyelitis involved being immobilized and sent away from home for surgical and physiotherapeutic treatment. Growing up in a social context that was often tough and unfriendly resulted in the development of strategies, such as optimistic thinking, trying to blend in, trusting one's ability to manage, and to handle the preconceptions and expectations of others. At the onset of late effects of polio, some of these strategies were still functioning, whereas overachieving, disregarding pain, and weariness were not. Conclusion: The challenges of growing up with a disability following paralytic polio led to the development of various psychological strategies for managing daily life. By understanding these experiences and strategies, knowledge may be gained in assisting rehabilitation professionals to better support persons with late effects of polio in adapting to the new situation. Implications for rehabilitation: At the onset of late effects of polio, strategies developed earlier in life, such as overachieving, disregarding pain, and weariness, may not function anymore. Understanding the experiences of growing up with poliomyelitis can support rehabilitation professionals to provide targeted interventions for people with late effects of polio and enable them to develop new adaptive strategies. Developing new strategies, such as accepting increased symptoms, and augmenting self-esteem and self-efficacy, may improve daily functioning among people with late effects of polio.